Karakteristik Burung dalam Perspektif Al-Qur’an dan Sains - Afrizal El Adzim Syahputra; Abdur Rohman (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2022)
Birds are the animals most frequently mentioned in the Qur’an. However, the birds in the Qur’an have never been studied using a comprehensive scientific approach. This research is expected to be able to add insight and knowledge to Indonesian scholars about the integration of the theme of birds in the Qur’an and science. This study uses a thematic method based on library research by tracing verses about birds in the Qur’an. These verses are then studied using the method of scientific exegesis in which the sources are contemporary commentary books. Then these verses can be integrated with science. Based on the research conducted by the author, the characteristics of birds in the Qur’an can be detailed as follows: First; movement of birds in the air. For thousands of years before, the Qur’an has explained the patterns of bird movement that have been revealed by science today. Second; the behavior of crows and their benefits to humans. Crows have intelligence that is beneficial to human life. Third; nutritional content in salwa birds. The nutritional value of salwa birds can nourish the human body. Fourth; the behavior of the birds bombarding Abraha’s troops. Based on the opinion of contemporary scholars, these birds are interpreted as small organisms that cause various diseases. This organism then develops into a lethal weapon of mass murder, which is popularly known as bioterrorism.